2002
DOI: 10.1007/s00428-002-0705-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of p53, p63, and p73 in benign salivary gland tumors

Abstract: The tumor-suppressor protein p53 has recently been shown to belong to a family that includes two structurally related proteins, p63 and p73. In contrast to p53, p63 and p73 play an essential role in epithelial development, stem cell identity and cellular differentiation. Salivary gland tumors carry a wide spectrum of histopathological forms, which may share a common single-cell origin from the epithelial progenitor basal duct cells and have a different tendency of malignant progression. This study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
3
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 19 publications
3
44
3
6
Order By: Relevance
“…Salivary pleomorphic adenomas frequently showed the coexpression of CKs and vimentin, and moreover, neoplastic myoepithelial cells in these tumors revealed positivity for p63. 16,17 Such findings supported that matrix-producing carcinoma of the breast was associated with myoepithelial cell-like differentiation: although the metaplastic cells of matrixproducing carcinoma have myoepithelial cell-like features, the origin of this cancer is considered to be derived from mammary epithelial cells. A recent report showed that CD99 (MIC2) was expressed in breast carcinoma, especially in matrix-producing carcinoma, but concluded that there was no significance between CD99 (MIC2) expression and the proliferating rate or nodal status; 18 however, it was suggested that CD99 (MIC2) expression was a useful marker to differentiate metaplastic carcinomas from primary or metastatic sarcomas of the breast, although its biological significance remains unclear.…”
Section: Discussionmentioning
confidence: 69%
“…Salivary pleomorphic adenomas frequently showed the coexpression of CKs and vimentin, and moreover, neoplastic myoepithelial cells in these tumors revealed positivity for p63. 16,17 Such findings supported that matrix-producing carcinoma of the breast was associated with myoepithelial cell-like differentiation: although the metaplastic cells of matrixproducing carcinoma have myoepithelial cell-like features, the origin of this cancer is considered to be derived from mammary epithelial cells. A recent report showed that CD99 (MIC2) was expressed in breast carcinoma, especially in matrix-producing carcinoma, but concluded that there was no significance between CD99 (MIC2) expression and the proliferating rate or nodal status; 18 however, it was suggested that CD99 (MIC2) expression was a useful marker to differentiate metaplastic carcinomas from primary or metastatic sarcomas of the breast, although its biological significance remains unclear.…”
Section: Discussionmentioning
confidence: 69%
“…Benign myoepithelial cells of salivary gland, like those of normal breast and prostate epithelium, express p63. 21 Di Como et al 9 reported p63 expression in four pleomorphic adenomas and two of four carcinomas of the salivary glands. Bilal et al found that for all salivary gland-derived tumor types that differentiated towards luminal and myoepithelial lineages (pleomorphic adenomas, basal cell adenomas, and adenoid cystic carcinomas), p63 was expressed in myoepithelial cells, whereas internal luminal cells were always negative.…”
mentioning
confidence: 97%
“…SSCP can miss mutations detected by direct sequencing. Weber and co-workers analyzed TP53 mutations by direct sequencing of exons 4-9 and detected mutations in 4/42 PA and 3/12 myoepitheliomas [14]. Despite the evidence that TP53 might be altered in SGN [10,13,14,16,17,18], we sequenced all of our samples and found only four missense mutations, one nonsense TP53 mutation and a very low frequency of LOH at the 17p 13.1 region in our subset of salivary tumor samples.…”
Section: Discussionmentioning
confidence: 70%
“…Previous papers reported positive immunoexpression of p53 protein [8,9], yet TP53 mutations seem to be infrequent events in pleomorphic adenomas (PA), adenoid cystic carcinomas (ACC), mucoepidermoid carcinomas (MEC) and carcinomas ex pleomorphic adenomas (CAexPA) [10,11,12,13,14]. These previous papers relied on different techniques (SSCP, for example, which misses mutations when compared to direct sequencing), and in some of them, sequencing was only performed on a few samples.…”
Section: Introductionmentioning
confidence: 99%